Rhythms of insect evolution : evidence from the Jurassic and Cretaceous in northern China /: evidence from the Jurassic and Cretaceous in northern China. (2019) - Ren, Dong, 1963-; Gao, Taiping, 1984-; Shih, Chung Kun; Yao, Yunzhi; (Paleoentomologist), Wang, Yongjie
No abstract available